2022
DOI: 10.1007/s11033-022-08231-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2

Abstract: Background BSG (CD147) is a member of the immunoglobulin superfamily that shows roles for potential prognostics and therapeutics for metastatic cancers and SARS-CoV-2 invasion for COVID-19. The susceptibility of malignant cancers to SARS-CoV-2 as well as the correlations between disease outcome and BSG expression in tumor tissues have not been studied in depth. Methods In this study, we explored the BSG expression profile, survival correlation, DNA methylation, mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…IHC was performed using formalin-fixed, paraffin-embedded sections of breast and lung cancer tissues obtained from Chinese patients was performed as previously described ( 47 , 56 - 60 ). DPP4 antibody (1:100 dilution) was used in IHC.…”
Section: Methodsmentioning
confidence: 99%
“…IHC was performed using formalin-fixed, paraffin-embedded sections of breast and lung cancer tissues obtained from Chinese patients was performed as previously described ( 47 , 56 - 60 ). DPP4 antibody (1:100 dilution) was used in IHC.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were inoculated in 12-well plates and treated with CD at final concentrations of 0, 10, 20, and 40 µM for 24 h. Protein was collected, and expression levels were monitored by Western blot. Total RNA was extracted by reverse transcription ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification was conducted using a Veriti 96-well thermal cycler (ABI, USA); it is worth noting that the amplification number for SOX9 did not exceed 30 cycles. After PCR reactions were completed, agarose electrophoresis for the amplified products was performed on 1.5% agarose gel ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Glucose related protein 78 (GRP78) promotes viral entry by working itself as a receptor or by stabilizing the binding between the spike protein and ACE2 [73] , [74] . Both CD147 and GRP78 are tumour markers [75] , [76] , indicating why cancer patients have a higher risk of severe COVID-19 [77] . Furthermore, it was recently shown that the expression of GRP78 is increased in the jejunum of rats fed a high fat diet [78] .…”
Section: Other Receptors and Factors Involved In Sars-cov-2 Infectionmentioning
confidence: 99%